Effect of a Novel Patient Garment on Perceived Privacy during Colonoscopy: A Simple Approach to Minimize Embarrassment. (27th January 2019) - Aamar, Ali; Butt, Zeeshan; Madhani, Kamraan; Hussain, Iqra; Garsten, Joel; Aslanian, Harry
Abstract : Background . In the United States, patients wear a one-piece, reusable cloth gown during colonoscopy procedures. Many patients report embarrassment related to bodily exposure during colonoscopy. This may limit participation in colorectal cancer screening programs. Aims . To assess whether the use of a novel, disposable patient garment (Privacy Pants, Jackson, MS), which increases patient coverage, can reduce embarrassment related to bodily exposure and increase colonoscopy acceptance rates. Methods . Patients were offered a novel gown, and they completed questionnaires before and after colonoscopy. Results . A total of 120 patients participated. 54% were female and 82% were Caucasian. The novel gown had high overall satisfaction (8.3) and was associated with a sense of respect during the procedure (9.4). 67% (80) of the patients had a prior colonoscopy, and of these, 76% would request a novel gown over a traditional gown for future procedures. Among all study participants, a high rate of acceptability for repeat colonoscopy if recommended by their doctors was reported (mean of 9.4). Nonwhites were more likely to have a concern for embarrassment addressed by using novel gowns as compared to whites (P value 0.02). Conclusion . All participants, particularly women and nonwhite participants, reported high rates of respect and satisfaction and decrease in embarrassment utilizing the novel gown during colonoscopy. Patients who had prior colonoscopy with a traditional gown preferred the novel garment. A novel procedure gown may enhance colonoscopy acceptance by minimizing embarrassment.